Genetics and genomics of uniformity and resilience in livestock and aquaculture species: A review - Iung, Laiza Helena de Souza [UNESP]; Carvalheiro, Roberto [UNESP]; Neves, Haroldo Henrique de Rezende; Mulder, Herman Arend (Wiley, 2020)
Genetic control of residual variance offers opportunities to increase uniformity and resilience of livestock and aquaculture species. Improving uniformity and resilience of animals will improve health and welfare of animals and lead to more homogenous products. Our aims in this review were to summarize the current models and methods to study genetic control of residual variance, genetic parameters and genomic results for residual variance and discuss future research directions. Typically, the genetic coefficient of variation is high (median = 0.27; range 0–0.86) and the heritability of residual variance is low (median = 0.01; range 0–0.10). Higher heritabilities can be achieved when increasing the number of records per animal. Divergent selection experiments have supported the feasibility of selecting for high or low residual variance. Genomic studies have revealed associations in regions related to stress, including those from the heat shock protein family. Although the number of studies is growing, genetic control of residual variance is still poorly understood, but big data and genomics offer great opportunities.
Keywords: genetic control of residual variance; genetic heterogeneity of residual variance; micro-environmental sensitivity; resilience; uniformity